Strategic debt management within the stability and growth pact - Gernot Sieg; Ulrike Stegemann (Technische Universität Braunschweig, Institut für Volkswirtschaftslehre, 2009)
Opportunistic politicians use the composition of public debt as a signal for competence. A competent government will not issue long-term nominal debt, as optimal to balance the budget, but long-term inflation-indexed debt. We consider politicians that pursue the objective of a balanced budget subject to the Stability and Growth Pact and reelection. A government's competence is reflected by its ability to produce a public service at a lower cost (taxes). Competence is private information of politicians.
Keywords: D72; H63; E32; 330; Political Budget Cycle; Debt Management; Inflation-indexed Bonds; Stability and Growth Pact; Debt Management; Haushaltskonsolidierung; EU-Stabilitätspakt; Public Choice; EU-Staaten